Tyre for vehicle carrying heavy loads

A tire composition with highly saturated ethylene and 1,3-butadiene copolymers and carbon black achieves improved wet grip and balanced durability and rolling resistance, addressing the trade-offs in existing tire technologies.

CN120322496APending Publication Date: 2025-07-15MICHELIN & CO (CIE GEN DES ESTAB MICHELIN)
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202380079426.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-12
Filing Date
2023-12-05
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

The prior art is difficult to improve wet grip performance while maintaining the wear resistance and rolling resistance properties of the tire, especially in rubber compositions using highly saturated diene elastomers.

Method used

Using a rubber composition containing a highly saturated ethylene and 1,3-butadiene statistical copolymer of more than 50 phr, the reinforcement filler is mainly carbon black, and the carbon black content is above 90% and the ethylene unit content is between 55-65 mol%, to optimize the microstructure of the rubber composition to improve performance trade-offs.

Benefits of technology

It significantly improves the wet grip performance of the tire while maintaining a good trade-off between wear resistance and rolling resistance performance, providing better comprehensive performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005403840400000041
    Figure BDA0005403840400000041
  • Figure BDA0005403840400000101
    Figure BDA0005403840400000101
  • Figure BDA0005403840400000131
    Figure BDA0005403840400000131
Patent Text Reader

Abstract

The invention relates to a tyre intended to fit for vehicles carrying heavy loads, said tyre comprising a tread, the portion of which intended to come into contact with the ground on which the tyre travels being formed entirely or partially from a rubber composition comprising more than 50 phr of a highly saturated diene elastomer and between 30 phr and 55 phr of a reinforcing filler, the present invention relates to a composition comprising a highly saturated diene elastomer, which is an angelica-free copolymer of ethylene and 1, 3-butadiene and comprises between 55 mol% and 65 mol% of ethylene units, and a reinforcing filler comprising carbon black in a mass content greater than 90% and less than or equal to 100% by weight of the reinforcing filler. The tire provided by the invention has good balance among wet road holding performance, wear resistance and rolling resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Field of the Invention

[0001] The field of the invention is that of the assembly of tires for vehicles intended to carry heavy loads, the tread of which is wholly or partly composed of a rubber composition reinforced with carbon black and rich in highly saturated diene elastomers. Background Art

[0002] Tires must meet a large number of often opposing technical requirements, including high wear resistance, low rolling resistance and high grip.

[0003] It is known that the grip performance of a tire can be improved by increasing the contact surface of the tread on the ground on which the tire rolls. One solution consists in using a highly deformable tread, in particular a very soft rubber composition, which constitutes the surface of the tread intended to come into contact with the rolling surface. Although it contributes to grip, the use of a very soft rubber composition can lead to a decrease in the wear resistance of the tire. Specifically, it is known that in order to improve wear resistance, a certain stiffness of the tread is desirable, which can be obtained, for example, by increasing the content of reinforcing fillers in the rubber compositions constituting these treads to strengthen the tread. Unfortunately, experience has shown that this strengthening of the tread unfavorably affects the rolling resistance properties in a known way (usually in a prohibitive way) due to a significant increase in the hysteresis losses of the rubber composition. It is also known in practice that a low hysteresis of the rubber composition is required to minimize the rolling resistance, while a dissipative rubber composition favors the grip performance.

[0004] To improve the compromise between wear resistance and rolling resistance, it is proposed in WO 2014114607 A1 that highly saturated diene elastomers should be used in the rubber compositions of tires, such as copolymers of ethylene and 1,3-butadiene containing more than 50 mol% of ethylene units. However, there is still a need to improve the wet grip performance of tires the treads of which are formed from rubber compositions containing highly saturated diene elastomers, while maintaining a good compromise between wear resistance performance and rolling resistance performance. Summary of the Invention

[0005] This object is achieved because the inventors have found that a specific rubber composition can provide a tire having an improved compromise between wet grip performance, wear resistance and rolling resistance (in particular having improved wet grip performance while maintaining a good compromise between wear resistance performance and rolling resistance performance).

[0006] Thus, a subject of the present invention is a tire intended to be mounted on a vehicle carrying heavy loads, said tire comprising a tread, the part of said tread intended to be in contact with the ground on which the tire rolls being entirely or partly formed of such a rubber composition comprising more than 50 phr of a highly saturated diene elastomer, between 30 phr and 55 phr of a reinforcing filler, said highly saturated diene elastomer being a statistical copolymer of ethylene and 1,3 - butadiene and comprising between 55 mol% and 65 mol% of ethylene units, said reinforcing filler comprising carbon black in a mass content greater than 90% and less than or equal to 100% of the mass of the reinforcing filler. Detailed description

[0007] Any numerical interval expressed by the expression "between a and b" represents a numerical range greater than "a" and less than "b" (i.e., the extreme limits a and b are not included), while any numerical interval expressed by the expression "from a to b" means a numerical range extending from "a" up to "b" (i.e., the strict limits a and b are included).

[0008] The abbreviation "phr" means parts by weight per hundred parts of elastomer (if there are several elastomers, the sum of the elastomers).

[0009] The compounds mentioned in the specification may be compounds of fossil origin or may be bio - based compounds. In the case of bio - based compounds, they may be partly or entirely derived from biomass or obtained from renewable raw materials derived from biomass. Similarly, the compounds mentioned may also be derived from the recycling of materials already used, i.e., they may be partly or entirely derived from recycling processes or obtained from raw materials themselves derived from recycling processes.

[0010] In the present invention, "tire" is understood to mean a pneumatic tire or a non - pneumatic tire. A pneumatic tire generally comprises two beads, a crown and two sidewalls, said beads being intended to be in contact with a rim, said crown being constituted by at least one crown reinforcement and a tread, and said tire being reinforced by a carcass reinforcement anchored in the two beads. A non - pneumatic tire generally itself comprises, for example, a base designed to be mounted on a rigid rim, a crown reinforcement ensuring the connection with the tread and a deformable structure (such as spokes, ribs or cells) arranged between the base and the crown. Such a non - pneumatic tire does not necessarily include sidewalls. Non - pneumatic tires are described, for example, in documents WO03 / 018332 and FR2898077. According to any one embodiment of the present invention, the tire according to the present invention is preferably a pneumatic tire.

[0011] Unless otherwise stated, the content of the units obtained by inserting monomers into a copolymer (such as the highly saturated diene elastomer for the purposes of the present invention) is expressed as a mole percentage relative to the total number of monomer units of the copolymer.

[0012] In a known manner, the term "ethylene unit" denotes a -(CH2-CH2)- unit obtained by inserting ethylene into the copolymer chain.

[0013] The highly saturated diene elastomer for the purposes of the present invention is a statistical copolymer of ethylene and 1,3-butadiene, which means that the statistically distributed monomer units of the copolymer are the monomer units resulting from the copolymerization of ethylene and 1,3-butadiene. Thus, the copolymer contains ethylene units and butadiene units. It is known that an ethylene unit is a monomer unit having the structure -(CH2-CH2)-. It is also known that a butadiene unit is a monomer unit having the structure -CH2-CH(CH=CH2)- (1,2 unit) or -CH2-CH=CH-CH2- (1,4 unit), depending on whether the 1,3-butadiene monomer is inserted into the polymer chain by 1,2-addition or 1,4-addition during the polymerization reaction. The molar content of ethylene units in the highly saturated diene elastomer is greater than 55% and less than 65% of the monomer units of the highly saturated diene elastomer. Outside the range defining the ethylene unit content according to the present invention, the performance compromise between wet grip, rolling resistance and abrasion resistance is not good. For values equal to or less than 55%, the abrasion resistance performance decreases; for values greater than or equal to 65%, the wet grip performance decreases. The molar content of ethylene units in the highly saturated diene elastomer is preferably greater than 55% and less than or equal to 63% of the monomer units of the highly saturated diene elastomer, more preferably greater than or equal to 58% and less than or equal to 62% of the monomer units of the highly saturated diene elastomer.

[0014] Highly saturated diene elastomers can be obtained according to various synthesis methods known to those skilled in the art, in particular based on the microstructure of the highly saturated diene elastomer sought. Generally, it can be prepared by copolymerization of 1,3-butadiene and ethylene according to known synthesis methods, in particular in the presence of a catalytic system comprising a metallocene complex. In this regard, mention may be made of the catalytic systems based on metallocene complexes described in EP 1092731 A1, WO 2004 / 035639 A1, WO 2007 / 054223 A2 and WO 2007 / 054224 A2 in the name of the applicant. Highly saturated diene elastomers can also be prepared by using a method of a preformed type of catalytic system (such as the catalytic systems described in WO 2017 / 093654 A1, WO 2018 / 020122 A1 and WO 2018 / 020123 A1). Advantageously, the diene elastomers are prepared according to a semi-continuous or continuous method as described in WO 2017 / 103543 A1, WO 2017 / 103544 A1, WO 2018 / 193193 A1 and WO 2018 / 193194 A1.

[0015] The highly saturated diene elastomer preferably contains units of formula (I) or units of formula (II) (1,2 units).

[0016]

[0017] -CH2-CH(CH=CH2)- (II)

[0018] The presence of the saturated six-membered cyclic units of formula (I) (1,2-cyclohexane units) in the copolymer may result from a series of very specific insertions of ethylene and 1,3-butadiene in the polymer chain during the growth of the polymer chain. When the highly saturated diene elastomer contains units of formula (I) or units of formula (II), the mole percentages (o and p respectively) of the units of formula (I) and the units of formula (II) in the highly saturated diene elastomer preferably satisfy the following equation (Equation 1) or equation (Equation 2), calculating o and p based on all monomer units of the highly saturated diene elastomer.

[0019] 0 < o + p ≤ 30 (Equation 1)

[0020] 0 < o + p < 25 (Equation 2)

[0021] Preferably, the highly saturated diene elastomer contains units of formula (I) with a molar content greater than 0 mol% and less than 15 mol%, more preferably less than 10 mol%, calculating the mole percentage based on all monomer units of the highly saturated diene elastomer.

[0022] According to a particularly preferred embodiment, the highly saturated diene elastomer comprises 1,4-units in the trans configuration (1,4-trans units). When the diene elastomer comprises 1,4-trans units, the 1,4-trans units account for more than 50 mol% of the 1,4-units of the highly saturated diene elastomer, preferably more than 80 mol% of the 1,4-units of the highly saturated diene elastomer.

[0023] The highly saturated diene elastomer may consist of a mixture of highly saturated diene elastomers that differ from one another in microstructure or macrostructure.

[0024] The content of the highly saturated diene elastomer in the rubber composition is greater than 50 parts by weight per hundred parts by weight of elastomer of the rubber composition (phr). It generally varies in the range from greater than 50 phr up to 100 phr. Below the shown minimum value, the target technical effect is insufficient. The higher the content of the highly saturated diene elastomer in the rubber composition, the better the sought technical effect.

[0025] When the highly saturated diene elastomer consists of a mixture of highly saturated diene elastomers that differ from one another in microstructure or macrostructure, the content of the highly saturated diene elastomer in the rubber composition relates to the mixture of highly saturated diene elastomers.

[0026] In addition to the highly saturated diene elastomer, the rubber composition may further comprise a second diene elastomer. A diene elastomer is understood to mean an elastomer that consists at least in part (i.e., a homopolymer or copolymer) of diene monomer units (monomers having two conjugated or non-conjugated carbon-carbon double bonds). The second elastomer may be selected from highly unsaturated diene elastomers consisting of polybutadiene, polyisoprene, butadiene copolymers, isoprene copolymers, and mixtures thereof. A highly unsaturated diene elastomer denotes an elastomer that contains more than 50 mol% of diene units.

[0027] The content of the highly saturated diene elastomer in the rubber composition is preferably greater than 80 phr, more preferably greater than 90 phr, and advantageously equal to 100 phr.

[0028] The rubber composition contains any type of "reinforcing" filler known to be capable of reinforcing a rubber composition that can be used in particular for the production of tyre treads. Such reinforcing fillers generally consist of nanoparticles with an (weight) average size of less than one micrometre, usually less than 500 nm, most usually between 20 nm and 200 nm, particularly and more preferably between 20 nm and 150 nm. The content of the reinforcing filler in the rubber composition is between 30 phr and 55 phr, preferably in the range from 35 phr to 50 phr, more preferably in the range from 35 phr to 45 phr. The reinforcing filler contains from more than 90 mass % up to 100 mass % of carbon black, the mass percentages being calculated relative to the mass of the reinforcing filler of the rubber composition. Preferably, the mass content of carbon black in the rubber composition is greater than 95 % and less than or equal to 100 % of the mass of the reinforcing filler in the rubber composition. When the mass content of carbon black in the rubber composition is less than 100 % of the mass of the reinforcing filler in the rubber composition, the reinforcing filler may then contain, in addition to carbon black, any type of filler known to be capable of reinforcing a rubber composition that can be used for the manufacture of tyres, such as reinforcing inorganic fillers (such as silica combined in a known manner with a coupling agent). Advantageously, the mass content of carbon black in the rubber composition is equal to 100 % of the mass of the reinforcing filler in the rubber composition.

[0029] Preferably, the BET specific surface area of the carbon black is greater than 90 m 2 / g. More preferably, the BET specific surface area of the carbon black is greater than 100 m 2 / g. Preferably, the specific surface area of the carbon black is less than 145 m 2 / g. The BET specific surface area is generally measured according to standard ASTM D6556-09 [multi-point method (5 points) - gas: nitrogen - relative pressure range P / P0: 0.05 to 0.30].

[0030] Preferably, the rubber composition contains from 0 phr to less than 5 phr of a plasticizer selected from liquid plasticizers, plasticized hydrocarbon resins and mixtures thereof. In other words, the total content of plasticizer (whether liquid plasticizer, plasticized hydrocarbon resin or mixture thereof) in the rubber composition is preferably in the range from 0 phr to less than 5 phr, more preferably from 0 phr to less than 3 phr, still more preferably equal to 0 phr.

[0031] A plasticizer is considered to be liquid when it has the ability to ultimately assume the shape of its container at 23 °C, this definition being contrary to that of a plasticized resin which is essentially solid at ambient temperature. As liquid plasticizers, mention may be made of vegetable oils, mineral oils, ethers, esters, phosphate or sulphonate plasticizers and mixtures thereof.

[0032] Plasticized hydrocarbon resins are polymers well known to those skilled in the art. They are essentially based on carbon and hydrogen atoms, but may contain other types of atoms (such as oxygen), and can be used specifically as plasticizers or tackifiers in polymer matrices. They are essentially at least partially miscible (i.e., compatible) with the polymer compositions in which the hydrocarbon resins are intended to be used at the contents employed, thus acting as true diluents. They have been described, for example, in the book "Hydrocarbon Resins" by R. Mildenberg, M. Zander, and G. Collin (New York, VCH, 1997, ISBN 3-527-28617-9), and Chapter 5 of said book deals with their applications, especially in the field of tire rubber engineering (5.5. "Rubber Tires and Mechanical Goods"). In a known manner, since hydrocarbon resins soften upon heating and can thus be molded, these hydrocarbon resins can also be described as thermoplastic resins.

[0033] Preferably, the rubber composition does not contain reinforcing resins (also known as "resin curing"). Reinforcing resins are described, for example, in the literature "Compounding and Vulcanization" by R. Rajesh Babu, G. S. Shibulal, Arup K. Chandra, and Kinsuk Naskar ("Advances in Elastomers", pp. 83-135, 2013, published by Springer) and WO 02 / 10269A2. It is known that they increase the stiffness of the rubber composition by generating a three-dimensional network in the rubber composition after curing of the rubber composition. The most common reinforcing resins are those using a two-component system based on phenolic compounds (such as phenol or resorcinol derivatives) and methylene donors (such as hexamethylenetetramine (HMT)).

[0034] The rubber composition may also contain all or some of the common additives usually used in elastomeric compositions intended to form the tread, such as crosslinking agents, pigments, protective agents (such as antiozonant waxes, chemical antiozonants, and antioxidants).

[0035] The rubber composition preferably contains a vulcanization system according to any one of the embodiments of the present invention. The vulcanization system generally contains sulfur and vulcanization accelerators.

[0036] Sulfur is usually provided in the form of molecular sulfur or a sulfur donor, preferably in molecular form. Molecular sulfur is also referred to as elemental sulfur. The term "sulfur donor" is understood to mean any compound that releases sulfur atoms, which may or may not be bound in the form of a polysulfide chain and is capable of inserting into and bridging elastomer chains in the polysulfide chains formed during vulcanization. The sulfur content in the rubber composition is preferably less than 2 phr, preferably between 0.3 phr and 1.5 phr.

[0037] As (primary or secondary) vulcanization accelerators, any compound capable of acting as a vulcanization accelerator for diene elastomers in the presence of sulfur can be used, in particular accelerators of the thiazole type and their derivatives, sulfenamide type accelerators (primary accelerators), or accelerators of the guanidine, thiuram, dithiocarbamate, dithiophosphate, thiourea, and xanthate types (secondary accelerators). The term "guanidine" denotes any compound containing the divalent group -HN-C(=NH)-NH-. The guanidine is preferably diphenylguanidine. The vulcanization accelerators are used in a preferred content between 0.3 phr and 5 phr, more preferably between 0.5 phr and 2.5 phr.

[0038] As examples of primary accelerators, sulfenamide compounds can be particularly mentioned, such as N-cyclohexyl-2-benzothiazole sulfenamide ("CBS"), N,N-dicyclohexyl-2-benzothiazole sulfenamide ("DCBS"), N-tert-butyl-2-benzothiazole sulfenamide ("TBBS"), and mixtures of these compounds. The primary accelerator is preferably a sulfenamide, more preferably N-cyclohexyl-2-benzothiazole sulfenamide.

[0039] Examples of secondary accelerators particularly include thiuram polysulfides, preferably thiuram disulfides, such as tetraethylthiuram disulfide, tetrabutylthiuram disulfide (TBTD), tetrabenzylthiuram disulfide (TBZTD), and mixtures of these compounds. The secondary accelerator is preferably thiuram disulfide, more preferably tetrabenzylthiuram disulfide.

[0040] The primary accelerator is preferably a sulfenamide. When the primary vulcanization accelerator is a sulfenamide, it is preferably N-cyclohexyl-2-benzothiazole sulfenamide.

[0041] The vulcanization accelerator is preferably a mixture of a primary accelerator and a secondary accelerator. The term "primary accelerator" means a single primary accelerator or a mixture of primary accelerators. Similarly, the term "secondary accelerator" means a single secondary accelerator or a mixture of secondary accelerators. When the vulcanization accelerator is a mixture of a primary accelerator and a secondary accelerator, the vulcanization accelerator is preferably a mixture of a sulfenamide and a thiuram disulfide, or a mixture of a sulfenamide, a thiuram disulfide and a guanidine. The sulfenamide is preferably N-cyclohexyl-2-benzothiazole sulfenamide, the thiuram disulfide is preferably tetrabenzyl thiuram disulfide, and the guanidine is preferably diphenyl guanidine.

[0042] In a known manner, the vulcanization system may also comprise a vulcanization activator, such as a metal oxide (e.g., zinc oxide) or a fatty acid (e.g., stearic acid).

[0043] The rubber composition can be manufactured in a suitable mixer using two consecutive preparation stages according to the general procedures known to those skilled in the art: a first stage of thermomechanical processing or kneading at a high temperature (sometimes called the "non-production" stage), the maximum temperature of which is between 110 °C and 190 °C, preferably between 130 °C and 180 °C, followed by a second stage of mechanical processing at a low temperature (usually below 110 °C, e.g., between 40 °C and 100 °C) (sometimes called the "production" stage), during which sulfur or a sulfur donor and a vulcanization accelerator are added during the course of the finishing stage.

[0044] As an example, the first stage (non-production) is carried out in a single thermomechanical step, during which all the necessary components, optional additional processing aids and various other additives except sulfur and the vulcanization accelerator are introduced into a suitable mixer (e.g., a conventional closed mixer). The total kneading time in this non-production stage is preferably between 1 minute and 15 minutes. After cooling the mixture obtained in the first non-production stage, sulfur and the vulcanization accelerator are then usually introduced at a low temperature in an open mixer (e.g., a mill); then, all the substances are mixed (production stage) for several minutes, e.g., between 2 minutes and 15 minutes.

[0045] When the vulcanization system comprises a primary accelerator and a secondary accelerator, the rubber composition is preferably manufactured by a method comprising a first step (step a)) and a second step (step b)). In step a), the components of the rubber composition other than sulfur and the primary accelerator are mixed by kneading (in particular thermomechanical mixing / kneading). In step b), sulfur and the primary accelerator are introduced into the kneaded mixture comprising an elastomer, a reinforcing filler and the secondary accelerator. During step a), the elastomer, the reinforcing filler and the secondary accelerator are usually kneaded together in a suitable mixer (such as a standard closed mixer). The kneading temperature in step a) is higher than 110 °C, preferably between 110 °C and 190 °C, advantageously higher than 130 °C and lower than 180 °C. The temperatures in the ranges between 110 °C and 190 °C and between 130 °C and 180 °C correspond to the highest temperature values reached by the mixture kneaded in the mixer during step a). Usually, the kneading in step a) continues until the kneaded mixture reaches the highest kneading temperature before being removed from the mixer. The total duration of kneading in step a) is preferably between 1 minute and 15 minutes. The mixture prepared at the end of step a) is recovered and then cooled to enable step b), which is carried out at a low temperature, in this case at a temperature below 110 °C, preferably between 40 °C and 100 °C. During step b), the introduction of sulfur and the primary accelerator into the rubber composition is usually accomplished by kneading in an open mixer (such as a mill), usually for a time between 2 minutes and 15 minutes. The kneading in step b) is carried out at a temperature below 110 °C, preferably between 40 °C and 100 °C.

[0046] Preferably, the rubber composition is extruded to form all or part of the tread profile of a tire. Then, during the assembly of the tire, radially from the outside inwards, it generally includes a tread, a crown reinforcement and a carcass reinforcement, and the tread is laid radially on the outside of the crown reinforcement. It is known that radially means the radial direction related to the axis of rotation of the tire.

[0047] The tire can be in an unprocessed form (i.e., before the step of curing the tire) or in a cured form (i.e., after the step of curing the tire). The tire is a tire for a vehicle for carrying heavy loads, in particular a tire for a heavy goods vehicle or a tire for a civil engineering vehicle, preferably a tire for a heavy goods vehicle.

[0048] In summary, the present invention can be implemented according to any one of the following embodiments 1 to 22:

[0049] Embodiment 1: A tire intended to be mounted on a vehicle carrying heavy loads, said tire comprising a tread, the part of the tread intended to be in contact with the ground on which the tire rolls being formed entirely or partly by such a rubber composition, said rubber composition comprising more than 50 phr of a highly saturated diene elastomer, reinforcing fillers between 30 phr and 55 phr, said highly saturated diene elastomer being a statistical copolymer of ethylene and 1,3-butadiene and comprising ethylene units between 55 mol% and 65 mol%, said reinforcing fillers comprising carbon black in a mass content greater than 90% and less than or equal to 100% of the mass of the reinforcing fillers.

[0050] Embodiment 2: The tire according to Embodiment 1, wherein the molar content of ethylene units in the highly saturated diene elastomer is greater than 55% of the monomer units of the highly saturated diene elastomer and less than or equal to 63% of the monomer units of the highly saturated diene elastomer.

[0051] Embodiment 3: The tire according to Embodiment 1 or 2, wherein the molar content of ethylene units in the highly saturated diene elastomer is greater than or equal to 58% of the monomer units of the highly saturated diene elastomer and less than or equal to 62% of the monomer units of the highly saturated diene elastomer.

[0052] Embodiment 4: The tire according to any one of Embodiments 1 to 3, wherein the highly saturated diene elastomer comprises units of formula (I) or units of formula (II).

[0053]

[0054] -CH2-CH(CH=CH2)- (II)

[0055] Embodiment 5: The rubber composition according to Embodiment 4, wherein the highly saturated diene elastomer comprises units of formula (I) in a molar content greater than 0% and less than 15%.

[0056] Embodiment 6: The tire according to any one of Embodiments 1 to 5, wherein the highly saturated diene elastomer comprises 1,4 units in a trans configuration, which represent more than 50 mol% of the 1,4 units of the highly saturated diene elastomer.

[0057] Embodiment 7: The tire according to any one of Embodiments 1 to 6, wherein the highly saturated diene elastomer comprises 1,4 units in a trans configuration, which represent more than 80 mol% of the 1,4 units of the highly saturated diene elastomer.

[0058] Embodiment 8: The tire according to any one of Embodiments 1 to 7, wherein the content of reinforcing fillers in the rubber composition ranges from 35 phr to 50 phr.

[0059] Embodiment 9: The tire according to any one of Embodiments 1 to 8, wherein the content of the reinforcing filler in the rubber composition ranges from 35 phr to 45 phr.

[0060] Embodiment 10: The tire according to any one of Embodiments 1 to 9, wherein the mass content of carbon black in the rubber composition is greater than 95% and less than or equal to 100% of the mass of the reinforcing filler.

[0061] Embodiment 11: The tire according to any one of Embodiments 1 to 10, wherein the BET specific surface area of the carbon black is greater than 90 m 2 / g.

[0062] Embodiment 12: The tire according to any one of Embodiments 1 to 11, wherein the BET specific surface area of the carbon black is greater than 100 m 2 / g.

[0063] Embodiment 13: The tire according to any one of Embodiments 1 to 12, wherein the BET specific surface area of the carbon black is less than 145 m 2 / g.

[0064] Embodiment 14: The tire according to any one of Embodiments 1 to 13, wherein the content of the highly saturated diene elastomer in the rubber composition is greater than 80 phr.

[0065] Embodiment 15: The tire according to any one of Embodiments 1 to 14, wherein the content of the highly saturated diene elastomer in the rubber composition is greater than 90 phr.

[0066] Embodiment 16: The tire according to any one of Embodiments 1 to 15, wherein the content of the highly saturated diene elastomer in the rubber composition is equal to 100 phr.

[0067] Embodiment 17: The tire according to any one of Embodiments 1 to 16, wherein the rubber composition contains 0 phr to less than 5 phr of a plasticizer selected from liquid plasticizers, plasticized hydrocarbon resins, and mixtures thereof.

[0068] Embodiment 18: The tire according to any one of Embodiments 1 to 17, wherein the rubber composition contains 0 phr to less than 3 phr of a plasticizer selected from liquid plasticizers, plasticized hydrocarbon resins, and mixtures thereof.

[0069] Embodiment 19: The tire according to any one of Embodiments 1 to 18, wherein the rubber composition contains 0 phr of a plasticizer selected from liquid plasticizers, plasticized hydrocarbon resins, and mixtures thereof.

[0070] Embodiment 20: The tire according to any one of Embodiments 1 to 19, wherein the rubber composition does not contain reinforcing resin.

[0071] Embodiment 21: The tire according to any one of Embodiments 1 to 20, wherein the tire is a tire for heavy goods vehicles or a tire for civil engineering vehicles.

[0072] Embodiment 22: The tire according to any one of Embodiments 1 to 21, wherein the tire is a tire for heavy goods vehicles.

[0073] The above and other features of the present invention will be more clearly understood by reading the following description of multiple exemplary embodiments of the present invention given as non-limiting illustrations.

[0074] Examples

[0075] Determination of the microstructure of elastomers by nuclear magnetic resonance (NMR):

[0076] By 1 H and 13 C NMR spectroscopy to characterize the copolymer of ethylene and 1,3-butadiene. NMR spectra were acquired on a Bruker Avance III 500 MHz spectrometer equipped with a 5 mm BBIz-class "broadband" cryoprobe. Quantitative 1 H NMR experiments used a 30° single pulse sequence and a 5 s repetition time between each acquisition. 64 to 256 accumulations were performed. Quantitative 13 C NMR experiments used a simple 30° pulse sequence with proton decoupling and a 10 s repetition time between each acquisition. 1024 to 10240 accumulations were performed. 1 H / 13 C two-dimensional experiments were used to determine the structure of the polymer. The determination of the microstructure of the copolymer was defined in the literature (article by Llauro et al., Macromolecules, 2001, 34, 6304 - 6311).

[0077] NMR measurements were carried out at 25 °C, where the copolymer was dissolved in a deuterated solvent (usually deuterated chloroform (CDCl3)) (about 25 mg of elastomer in 1 ml).

[0078] Size exclusion chromatography (SEC / RI):

[0079] Size Exclusion Chromatography (SEC) can fractionate polymer chains in solution based on their hydrodynamic volume. Like all chromatography systems, this technique is based on the elution of a solute (the polymer) through a column containing a stationary phase. The system consists, in order, of a solvent reservoir, a pump system, an injector, a set of columns, and a detector. The measurement system is equipped with a Waters Alliance e2695 module and a Waters fRI410 refractometer.

[0080] The mobile phase is eluted at a flow rate of 1 ml / min. The polymer is dissolved in THF at a concentration of 1 g / l. A volume of 100 μl is injected through a set of 3 Agilent size exclusion chromatography columns (Mixed B LS). The columns are maintained at a constant temperature of 35 °C in an oven. The stationary phase of the columns is based on a polystyrene / divinylbenzene gel with a controlled porosity. When dissolved in a solvent, the polymer chains are separated based on the hydrodynamic volume they occupy. The larger the volume they occupy, the fewer pores in the column they can reach, and the shorter the elution time. Detection is carried out by a refractometer (RI) maintained at 35 °C. Each elution volume is correlated with mass through molar calibration (calibrated against certified standards: polystyrene standards from Polymer Standard Service (Mainz)). Waters Empower software is used for data acquisition and analysis. Thus, the number-average molar mass (Mn), the weight-average molar mass (Mw), and the dispersity ( or PI = Mw / Mn) can be determined.

[0081] Glass transition temperature of the polymer:

[0082] The glass transition temperature (Tg) is measured by differential scanning calorimetry according to standard ASTM D3418 (1999).

[0083] Mooney viscosity:

[0084] The Mooney viscosity is measured using an oscillating consistency meter as described in standard ASTM D1646 (1999). The measurement is based on the following principle: The sample to be analyzed in the raw state (i.e., before curing) is molded (formed) in a cylindrical chamber heated to a given temperature (100 °C). After preheating for 1 minute, the rotor rotates at 2 revolutions per minute within the specimen, and the working torque required to maintain this motion is measured after 4 minutes of rotation. The Mooney viscosity (ML) is expressed in "Mooney units" (MU, 1 MU = 0.83 Newton·meter).

[0085] Dynamic properties:

[0086] Dynamic properties were measured on a viscometer (Metravib VA4000) according to standard ASTM D 5992-96. The response of a sample of the vulcanized composition (cylindrical specimen with a thickness of 4 mm and a cross-section of 400 mm 2 subjected to a simple alternating sinusoidal shear stress at a frequency of 10 Hz was recorded.

[0087] For the measurement of the complex dynamic shear modulus (G*) and the loss factor tanδ, a strain amplitude sweep was carried out at 60 °C from 0.1% to 100% peak-to-peak (outward cycle) and then from 100% to 0.1% peak-to-peak (return cycle). For the outward cycle, the maximum value of the observed tanδ (denoted as tanδ(max)) and the modulus G* at 50% deformation (denoted as G*50%) were shown. The smaller the value of G* at 50%, the more the abrasion resistance property is reduced; the larger the value of tanδ(max), the more the rolling resistance property is reduced.

[0088] For the measurement of tanδ(-20 °C), a temperature sweep was carried out at a stress of 0.7 MPa, and the value of tanδ observed at -20 °C was recorded. It will be recalled that, as is well known to those skilled in the art, this value represents the wet grip potential: the larger the value of tanδ(-20 °C), the better the wet grip.

[0089] Preparation of rubber compositions:

[0090] The elastomer, reinforcing filler, secondary accelerator, and various other components except sulfur and the primary accelerator were continuously introduced into a closed mixer with a volume of 3300 cm 3 (final filling level: approximately 70% by volume), and the initial vessel temperature of the closed mixer was approximately 50 °C. Then, thermomechanical processing (non-production stage) was carried out in one step, which lasted a total of approximately 3 to 4 minutes until a maximum "discharge" temperature of 160 °C was reached. The mixture thus obtained was recovered, cooled, and then sulfur and the primary accelerator were introduced into an open mixer (two-roll mill) at 30 °C, and all the substances were mixed (production stage) for 10 minutes.

[0091] Table 1 gives the breakdown of the formulation of the composition.

[0092] Table 1

[0093]

[0094]

[0095] (1) One of elastomers E1 to E6

[0096] (2) Carbon black N234 (BET of 120 m 2 / g)

[0097] (3) Anti-ozone wax (Varazon 4959 from Sasol Wax)

[0098] (4) N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (Santoflex 6PPD from Flexsys)

[0099] (5) Stearic acid (Pristerene 4931 from Uniqema)

[0100] (6) Technical grade zinc oxide from Umicore

[0101] (7) Diphenylguanidine (Perkacit DPG from Flexsys)

[0102] (8) Tetrabenzylthiuram disulfide (Perkacit TBZTD from Flexsys)

[0103] (9) N-cyclohexyl-2-benzothiazolesulfenamide (Santocure CBS from Flexsys)

[0104] Subsequently, the composition thus obtained is calendered into the form of a rubber sheet (with a thickness range of 2 mm to 3 mm) or a rubber film for measuring their physical or mechanical properties after vulcanization (cured state) at 140 °C, or into the form of a shaped element, which can be directly used as a semi-finished product for, for example, a tire after cutting and / or assembling into the desired dimensions.

[0105] Tires containing rubber compositions C1 to C3 in the tread do not conform to the present invention; tires containing rubber compositions C4 to C6 in the tread conform to the present invention. Compositions C1 to C3 respectively contain elastomers E1 to E3, which respectively contain 77% ethylene units, 74% ethylene units, and 68% ethylene units; compositions C4 to C6 respectively contain elastomers E4 to E6, in which the content of ethylene units is between 55% and 65%.

[0106] A statistical copolymer of ethylene and 1,3-butadiene (elastomers E1 to E6) is synthesized in the presence of a catalytic system according to the steps described below. The catalytic system contains a neodymium metallocene with an Mg / Nd molar ratio of 2.2 and an organomagnesium reagent. For the synthesis with an Mg / Nd molar ratio greater than 2.2 for polymerization, BOMAG is added to the polymerization medium.

[0107] All reagents are commercially available, except for the metallocene which can be prepared according to the procedure described in document WO 2007 / 054224. Butyl octyl magnesium BOMAG (20% heptane, C = 0.88 mol.l -1 ) is from Chemtura and is transferred and stored in a Schlenk tube under an inert atmosphere. Ethylene (grade N35) is from Air Liquide and can be used without prior purification.

[0108] The catalytic system is a preformed catalytic system. The catalytic system is prepared from 0.0065 mol / l of metallocene [Me2Si(Flu)2Nd(μ-BH4)2Li(THF)], the cocatalyst butyl octyl magnesium (BOMAG) (the BOMAG / Nd molar ratio is equal to 2.2), and the preformed monomer 1,3-butadiene (the 1,3-butadiene / Nd molar ratio is equal to 90) in methylcyclohexane. The medium is heated at 80 °C for 5 h. It is prepared according to the preparation method in Section II.1 of patent application WO 2017 / 093654 A1.

[0109] A copolymer (elastomer E1) of ethylene and 1,3-butadiene is synthesized according to the procedure described below.

[0110] Ethylene and 1,3-butadiene are polymerized according to a continuous process at 100 °C and 10 bar in a methylcyclohexane solution in the presence of a catalytic system (71 μmol Nd per 100 g of monomer). The mass concentration of the monomers fed to the reactor is 5.5%, the 1,3-butadiene / ethylene mass ratio is 0.4, and the active Mg / Nd molar ratio is 4.4.

[0111] When a desired conversion rate (71%) for obtaining a Mn of approximately 140,000 g / mol is used, a solution of antioxidants in methylcyclohexane (1 phr of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine and 0.9 phr of 2,2'-methylenebis(4-methyl-6-tert-butylphenol); phr = parts by weight per hundred parts by weight of elastomer) is used to terminate the polymerization at the outlet of the production line. The copolymer is recovered by a steam distillation process known to those skilled in the art as "stripping" and then dried on a worm machine equipped with a single screw.

[0112] The copolymer contains 77% ethylene units, 9% 1,2 units, 6% 1,4 units (more than 80% of the 1,4 units are 1,4-trans), and 8% cyclic units (1,2-cyclohexane units). Its transition temperature is -39 °C (ΔT is 10 °C, where ΔT is the temperature difference between the start and end of the glass transition), its Mn is 137,162 g / mol (PI is 1.72), and its ML(1+4) at 100 °C is 63.

[0113] A copolymer of ethylene and 1,3 - butadiene (elastomer E2) was synthesized according to the steps described below.

[0114] Ethylene and 1,3 - butadiene were polymerized according to a continuous process at 80 °C and 10 bar in a solution of methylcyclohexane in the presence of a catalytic system (81 μmol Nd per 100 g of monomers). The mass concentration of the monomers fed to the reactor was 6%, the 1,3 - butadiene / ethylene mass ratio was 0.5, and the active Mg / Nd molar ratio was 4.

[0115] At the desired conversion (71%) for obtaining an Mn of approximately 160000 g / mol, the polymerization was terminated at the outlet of the production line using a solution of antioxidants in methylcyclohexane (1 phr of N-(1,3 - dimethylbutyl)-N'-phenyl - p - phenylenediamine and 0.9 phr of 2,2'-methylenebis(4 - methyl - 6 - tert - butylphenol); phr = parts by weight per hundred parts by weight of elastomer). The copolymer was recovered by a steam distillation process known to those skilled in the art as "stripping" and then dried on a worm machine equipped with a single screw.

[0116] The copolymer contains 74% ethylene units, 7% 1,2 units, 12% 1,4 units (more than 80% of the 1,4 units are 1,4 - trans), and 7% cyclic units (1,2 - cyclohexane units). Its transition temperature is -44 °C (ΔT is 7 °C, where ΔT is the temperature difference between the start and end of the glass transition), its Mn is 154516 g / mol (PI is 1.70), and its ML(1 + 4) at 100 °C is 65.

[0117] A copolymer of ethylene and 1,3 - butadiene (elastomer E3) was synthesized according to the steps described below.

[0118] Ethylene and 1,3 - butadiene were polymerized according to a continuous process at 80 °C and 10 bar in a solution of methylcyclohexane in the presence of a catalytic system (119 μmol Nd per 100 g of monomers). The mass concentration of the monomers fed to the reactor was 7.5%, the 1,3 - butadiene / ethylene mass ratio was 0.8, and the active Mg / Nd molar ratio was 3.7.

[0119] At the desired conversion of Mn of about 160,000 g / mol (81%), the polymerization was terminated at the production line outlet using a solution of antioxidants in methylcyclohexane (0.8 phr of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine and 0.7 phr of 2,2'-methylenebis(4-methyl-6-tert-butylphenol); phr = parts by weight per hundred parts by weight of elastomer). The copolymer was recovered by a steam distillation process known to those skilled in the art as "stripping", and then dried on a worm machine equipped with a single screw.

[0120] The copolymer contains 68% ethylene units, 15% 1,2 units, 8.5% 1,4 units (more than 80% of the 1,4 units are 1,4-trans) and 8.5% cyclic units (1,2-cyclohexane units). Its transition temperature is -44 °C (ΔT is 5 °C, where ΔT is the temperature difference between the start and end of the glass transition), its Mn is 158,118 g / mol (PI is 1.82), and its ML(1+4) at 100 °C is 65.

[0121] A copolymer of ethylene and 1,3-butadiene (elastomer E4) was synthesized according to the procedure described below.

[0122] Ethylene and 1,3-butadiene were polymerized in a solution of methylcyclohexane at 80 °C and 10 bar according to a continuous process in the presence of a catalytic system (193 μmol Nd per 100 g of monomer). The mass concentration of the monomers fed to the reactor was 8.8%, the 1,3-butadiene / ethylene mass ratio was 1.45, and the active Mg / Nd molar ratio was 4.

[0123] At the desired conversion of Mn of 160,000 g / mol (81%), the polymerization was terminated at the production line outlet using a solution of antioxidants in methylcyclohexane (0.8 phr of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine and 0.7 phr of 2,2'-methylenebis(4-methyl-6-tert-butylphenol); phr = parts by weight per hundred parts by weight of elastomer). The copolymer was recovered by a steam distillation process known to those skilled in the art as "stripping", and then dried on a worm machine equipped with a single screw.

[0124] The copolymer contains 63% ethylene units, 21% 1,2 units, 9% 1,4 units (more than 80% of the 1,4 units are 1,4-trans) and 7% cyclic units (1,2-cyclohexane units). Its transition temperature is -42 °C (ΔT is 6 °C, where ΔT is the temperature difference between the start and end of the glass transition), its Mn is 158,877 g / mol (PI is 1.84), and its ML(1+4) at 100 °C is 65.

[0125] A copolymer of ethylene and 1,3-butadiene (elastomer E5) was synthesized according to the steps described below.

[0126] Ethylene and 1,3-butadiene were polymerized in a solution of methylcyclohexane at 80 °C and 10 bar according to a continuous process in the presence of a catalytic system (193 μmol Nd per 100 g of monomers). The mass concentration of the monomers fed to the reactor was 8.8%, the 1,3-butadiene / ethylene mass ratio was 1.47, and the active Mg / Nd molar ratio was 3.2.

[0127] At the desired conversion (67%) for obtaining an Mn of approximately 160,000 g / mol, the polymerization was terminated at the outlet of the production line using a solution of antioxidants in methylcyclohexane (0.8 phr of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine and 0.7 phr of 2,2'-methylenebis(4-methyl-6-tert-butylphenol); phr = parts by weight per hundred parts by weight of elastomer). The copolymer was recovered by a steam distillation process known to those skilled in the art as "stripping" and then dried on a worm machine equipped with a single screw.

[0128] The copolymer contains 62% ethylene units, 22% 1,2 units, 10% 1,4 units (more than 80% of the 1,4 units are 1,4-trans) and 6% cyclic units (1,2-cyclohexane units). Its transition temperature is -42 °C (ΔT is 6 °C, where ΔT is the temperature difference between the start and end of the glass transition), its Mn is 170,231 g / mol (PI is 1.70), and its ML(1+4) at 100 °C is 65.

[0129] A copolymer of ethylene and 1,3-butadiene (elastomer E6) was synthesized according to the steps described below.

[0130] Ethylene and 1,3-butadiene were polymerized in a solution of methylcyclohexane at 80 °C and 10 bar according to a continuous process in the presence of a catalytic system (154 μmol Nd per 100 g of monomers). The mass concentration of the monomers fed to the reactor was 15.5%, the 1,3-butadiene / ethylene mass ratio was 2.9, and the active Mg / Nd molar ratio was 2.2.

[0131] At the desired conversion of Mn of about 160,000 g / mol (46%), polymerization was terminated at the production line outlet using a solution of antioxidants in methylcyclohexane (0.8 phr of N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine and 0.7 phr of 2,2'-methylenebis(4-methyl-6-tert-butylphenol); phr = parts by weight per hundred parts by weight of elastomer). The copolymer was recovered by a steam distillation process known to those skilled in the art as "stripping" and then dried on a worm machine equipped with a single screw.

[0132] The copolymer contains 58% ethylene units, 26.5% 1,2 units, 11% 1,4 units (more than 80% of the 1,4 units are 1,4-trans) and 4.5% cyclic units (1,2-cyclohexane units). Its transition temperature is -41 °C (ΔT is 6 °C, where ΔT is the temperature difference between the start and end of the glass transition), its Mn is 167,092 g / mol (PI is 1.96), and its ML(1+4) at 100 °C is 68.

[0133] Results:

[0134] Table 2 gives the results. The results are expressed relative to a base of 100 for the control ([value of the composition considered / value of the control composition] × 100). Values greater than 100 represent values greater than those of the control.

[0135] Compositions C4 to C6 provide a performance compromise between wet grip, rolling resistance and abrasion resistance for the tire, which is far superior to Compositions C1 to C3; in particular, the wet grip performance is significantly improved while maintaining a good compromise between abrasion resistance performance and rolling resistance performance.

[0136] Table 2

[0137] Composition C1 C2 C3 C4 C5 C6 Elastomer E1 E2 E3 E4 E5 E6 tanδ max at 60 °C 99 103 100 102 98 100 G*50%,60℃ 103 99 100 103 103 98 tanδ at -20 °C, 0.7 MPa 81 79 100 110 121 124

Claims

1. A tire intended to be mounted on a vehicle for carrying heavy loads, said tire comprising a tread, the part of the tread intended to come into contact with the ground on which the tire rolls being entirely or partially formed of such a rubber composition comprising more than 50 phr of a highly saturated diene elastomer, reinforcing fillers between 30 phr and 55 phr, said highly saturated diene elastomer being a statistical copolymer of ethylene and 1,3 - butadiene and comprising between 55 mol% and 65 mol% of ethylene units, said reinforcing fillers comprising carbon black in a mass content greater than 90% and less than or equal to 100% of the mass of the reinforcing fillers.

2. The tire according to claim 1, wherein, The molar content of ethylene units in said highly saturated diene elastomer is greater than 55% of the monomer units of the highly saturated diene elastomer and less than or equal to 63% of the monomer units of the highly saturated diene elastomer, preferably greater than or equal to 58% of the monomer units of the highly saturated diene elastomer and less than or equal to 62% of the monomer units of the highly saturated diene elastomer.

3. The tire according to claim 1 or 2, wherein, Said highly saturated diene elastomer comprises units of formula (I) or units of formula (II) 4. The tire according to any one of claims 1 to 3, wherein, Said highly saturated diene elastomer comprises 1,4 - units in the trans configuration, which represent more than 50 mol% of the 1,4 - units of the highly saturated diene elastomer, preferably more than 80 mol% of the 1,4 - units of the highly saturated diene elastomer.

5. The tire according to any one of claims 1 to 4, wherein, The content of reinforcing fillers in said rubber composition ranges from 35 phr to 50 phr, preferably from 35 phr to 45 phr.

6. The tire according to any one of claims 1 to 5, wherein, The mass content of carbon black in said rubber composition is greater than 95% and less than or equal to 100% of the mass of the reinforcing fillers.

7. The tire according to any one of claims 1 to 6, wherein, The BET specific surface area of the carbon black is greater than 90 m 2 / g, preferably greater than 100 m 2 / g.

8. The tire according to any one of claims 1 to 7, wherein, The BET specific surface area of the carbon black is less than 145 m 2 / g.

9. The tire according to any one of claims 1 to 8, wherein, The content of highly saturated diene elastomer in said rubber composition is greater than 80 phr, preferably greater than 90 phr, more preferably equal to 100 phr.

10. The tire according to any one of claims 1 to 9, wherein, Said rubber composition comprises from 0 phr to less than 5 phr of a plasticizer selected from liquid plasticizers, plasticized hydrocarbon resins and mixtures thereof, preferably from 0 phr to less than 3 phr of a plasticizer selected from liquid plasticizers, plasticized hydrocarbon resins and mixtures thereof.

11. The tire according to any one of claims 1 to 10, wherein, Said rubber composition comprises 0 phr of a plasticizer selected from liquid plasticizers, plasticized hydrocarbon resins and mixtures thereof.

12. The tire according to any one of claims 1 to 11, wherein, Said rubber composition does not contain reinforcing resins.

13. A tire according to any one of claims 1 to 12, said tire being a tire for heavy goods vehicles or a tire for civil engineering vehicles, preferably a tire for heavy goods vehicles.

Citation Information

Patent Citations

  • Catalytic system, process for its preparation and that of an ethylene-conjugated diene copolymer

    EP1092731A1

  • Non pneumatic tire for use in motor vehicle wheel, has tire ribs cooperating with pockets introducing damping in case of deformation of ribs, where pockets are formed of walls delimiting volume filled with compressible material

    FR2898077A1

  • Running tread for tyre

    WO2002010269A2

  • Non-pneumatic tire

    WO2003018332A1

  • Ethylene / butadiene copolymers, catalytic system of producing same and production of said polymers

    WO2004035639A1